The Gambia - Poverty Reduction Strategy Paper Annual Progress Report and Joint IDA-IMF Staff Advisory Note - World Bank (World Bank, 2012)
The Gambian authorities completed the 2007 poverty reduction strategy paper (PRSP) annual progress report (APR) in October 2008. This is the first APR for the country's second PRSP, which covers the years 2007 to 2011.' The overall strategic priorities of the PRSP are: (i) macroeconomic stability and effective public resource management; (ii) promotion of pro-poor growth and employment through private sector development; (iii) improved basic social services; (iv) strengthened local communities and civil society organizations (CSOs); and (v) mainstreamed multisectoral programs on gender, environment, nutrition, and population. The PRSP incorporates programs focused on the Millennium Development Goals (MDGs). The APR is complemented by a 2008 report on progress towards the MDGs and a report which analyzes poverty related public expenditures in 2007. The APR analyzes key elements of the PRSP implementation, including macroeconomic performance, public sector reform, real sector performance such as agriculture and tourism, and the social sectors and crosscutting issues such as HIV/AIDS and gender.